MICROEMULSION TOPICAL FORMULATION OF ALLANTOIN AND DIFFUSION TEST FOR IN VITRO PERCUTANEOUS - Andriyani, Rina
Allantoin is an active substance that is present in a topical preparation. Recent research states that allantoin can increase the synthesis of pro-collagen. Because of the solubility properties owned allantoin, it will be difficult to pass through the stratum corneum layer which has a hydrophilic and hydrophobic part that is brick and mortar. The purpose of this study is to produce a formula allantoin in the microemulsion with type W/O that contains Virgin Coconut Oil (VCO), Tween 80, polyethyleneglycol 400 and glycerin. In vitro diffusion test, Batik Python snake skin used as a membrane. Method for making a microemulsion in this study by using the titration method and the Phase Inversion Temperature (PIT). Tools used to analyze the size of the globule is Transmission Electron Microscopy (TEM). Determination of levels of allantoin in microemulsion W/O using the method of High Performance Liquid Chromatography. From this study obtained two formulas microemulsion W/O are E.2.2 and E.2.3. Its have a range globule size between 130-500 nm. Based on t.tes-paired test using Microsoft Excel, to test the in vitro diffusion that differ significantly for the second formula in the 15 th minutes. The E.2.2 formula allantoin in the 15 th minutes to diffuse as much as 36.60 ± 51.40 mg/cm 2 , while the formula E.2.3 diffused as much as 267.36 ± 27.94 mg/cm 2 . Based on the results of the statistical analysis, it can be concluded that the formula is a formula E.2.3 better than formula E.2.2. The E.2.3 Formula consists of 0.5% allantoin, 12% aquadeion, 28.7% glycerol, 36% Tween 80, 1.2% PEG 400 and 21% VCO. In the stability test for 30 days with the parameters of pH and viscosity, also the 29 days to content determination parameter, statistical tests t.test-pairs, there was no significant difference for the both of formulas.